Implementasi Metode Montessori dalam Mengembangkan Ketrampilan Sosial Anak Sekolah Dasar - Habibatul Imamah (Al Ulya: Jurnal Pendidikan Islam, 2019)
Basically, children need meaningful activities, children like to take part in adult activities, so they feel useful and feel needed. The montessori method is based on the principle that a child's education must emerge and coincide with the stages of the child's development itself.The characteristics of this method are emphasizing the activities that are raised by the child and emphasizing the adjustment of the child's learning environment at the stage of its development. Social skills can be stimulated by various methods, one of which is the Montessori method. Through the Montessori method, children are trained to work together, have a sense of sympathy and empathy.This study aims to determine the learning process by using the Montessori method in improving social skills in elementary school children. This research uses descriptive qualitative method, with the focus of the research is the Implementation of the Montessori Method in improving the social skills of elementary school students. Data collection techniques using observation, interviews and documentation. And checking the validity of the data using triangulation. The results of the study showed that the implementation of the Montessori method in improving social skills of elementary school children was very effective. The environment is very instrumental in improving students' social skills. The results of the implementation of the Montessori method in improving children's social skills are shown by the children's concern for others, working together in completing tasks.